Evidence for anion-translocating plant uncoupling mitochondrial protein in potato mitochondria - Jezek, P; Costa, A D; Vercesi, A E (The Journal of biological chemistry, 1996)
Transport properties of plant mitochondria from potato tubers were investigated using the swelling technique and membrane potential measurements. Proton-dependent swelling of fatty acid-depleted mitochondria in potassium acetate with valinomycin was possible only in the presence of fatty acids (linoleic acid and 12-(4-azido-2-nitrophenylamino)dodecanoic acid) and was inhibited by various purine nucleotides including ATP, GDP, and GTP. Swelling representing uptake of hexanesulfonate was also inhibited by purine nucleotides. Also, the membrane potential of fatty acid-depleted potato mitochondria energized by succinate declined upon the addition of linoleic acid or 12-(4-azido-2-nitrophenylamino)dodecanoic acid, and this decrease was prevented by ATP and other purine nucleotides. These transport activities are identical to those reported for brown adipose tissue mitochondria and related to the uncoupling protein; therefore, we ascribed them to the plant mitochondrial uncoupling protein (PUMP). A major difference between plant and mammalian uncoupling protein is that PUMP transports small hydrophilic anions such as Cl- very slowly, if at all. We suggest that PUMP may play an important role in plant physiology, where a regulated uncoupling and thermogenesis can proceed during fruit and seed development.
Keywords: Fatty Acids; oxidativní fosforylace; Solanum tuberosum; zduření mitochondrií; Chlorides; Hydrogen-Ion Concentration; Intracellular Membranes; Membrane Potentials; Uncoupling Agents; rozpustnost; membránové potenciály; Biological Transport; Solubility; Ion Channels; Mitochondrial Swelling; mitochondrie; Carrier Proteins; chloridy; mitochondriální proteiny; uncoupling protein 1; mastné kyseliny; koncentrace vodíkových iontů; Alkanesulfonates; Mitochondria; biologický transport; Membrane Proteins; membránové proteiny; Uncoupling Protein 1; Mitochondrial Proteins; Oxidative Phosphorylation; intracelulární membrány; transportní proteiny; anionty; rozpřahující látky; alkylsulfonany; Anions; iontové kanály